Effect of experimentally increased nutrient availability on the structure, metabolic activities, and potential microbial functions of a maritime Antarctic microbial mat - Camacho, Antonio; Rochera, Carlos; Picazo, Antonio (Frontiers in Microbiology, 2022)
The role of competitive interactions based on resource utilisation was explored in a phototrophic microbial mat from Byers Peninsula (Maritime Antarctica). Shotgun metagenomic profiling of the mat showed a taxonomic and functional diverse microbial community. The heterotrophic bacterial community was dominated by Proteobacteria, where typically polar genera Janthinobacterium, Pseudomonas and Polaromonas dominated. Cyanobacteria, played a main role as primary producers, accompanied by diatoms and chlorophytes. To test the potential effects of the inorganic nutrients (N and P) availability on this community, a fully factorial nitrate and phosphorus addition experiment was conducted in situ. The mat exhibited a functional and structural response to the nutrient amendments. Compared to the undisturbed mat, phosphorus fertilisation favoured the growth of (non-heterocystous) cyanobacteria relative to that of diatoms, as indicated by changes in the carotenoid pigments biomarkers. Though no mat accretion was visible, fertilization improved the phototrophic activity and, mainly when P was amended, the production of exopolymeric substances was favoured, whereas further changes in the vertical distribution of primary production activity were observed as well. Illumina amplicon sequencing of the 16S rRNA gene also demonstrated changes in the relative abundance of heterotrophic prokaryotes, which were detectable from the phylum to the genus level, and mainly related to the amendment of nitrogen. Predictions made on the functional skills of these shifted prokaryotic communities indicated changes in abundance selecting taxa with a metabolic adaptation to the new nutrient scenarios. They mainly consisted in the enhancement of ecological strategies and metabolic regulatory mechanisms related with the uptake and metabolizing of either nitrogen or phosphorus, regulated by its availability whether in a balanced way or not. This study is pioneer in demonstrating how shifts in the regional dynamic of nutrients might alter the metabolic equilibrium of these initially considered homeostatic benthic communities. They can be accordingly considered as taxonomically diverse microbiomes with a functional repertoire still inclined to respond to the biogeochemical alteration of nutrient cycles, although occurring in a cold extreme environment where biological activity is partially restricted by environmental harshness.